Exploring the multifaceted bioactivities of Lavandula pinnata L. essential oil: promising pharmacological activities - Haddou, Mounir; Elbouzidi, Amine; Taibi, Mohamed; Baraich, Abdellah; Loukili, El Hassania; Bellaouchi, Reda; Saalaoui, Ennouaamane; Asehraou, Abdeslam; Salamatullah, Ahmad Mohammad; Bourhia, Mohammed; Nafidi, Hiba-Allah; Addi, Mohamed; et al. (Frontiers in Chemistry, 2024)
Introduction: This study investigates the biological activities of Lavandula pinnata essential oil (LPEO), an endemic lavender species from the Canary Islands, traditionally used in treating various ailments. Methods: LPEO was extracted by hydrodistillation and analyzed using GC-MS. Antioxidant activity was assessed by DPPH radical scavenging and total antioxidant capacity assays. Antimicrobial activity was evaluated by disc diffusion, MIC, MBC, and MFC determination against bacterial (Staphylococcus aureus, Micrococcus luteus, Escherichia coli, Pseudomonas aeruginosa) and fungal (Candida glabrata, Rhodotorula glutinis, Aspergillus niger, Penicillium digitatum) strains. Antidiabetic and anti-gout potential were investigated through α-amylase, α-glucosidase, and xanthine oxidase inhibition assays. Antityrosinase activity was determined using a modified dopachrome method. Cytotoxicity was assessed by MTT assay against breast (MCF-7, MDA-MB-468), liver (HepG2), colon (HCT-15) cancer cells, and normal cells (PBMCs). Results and discussion: LPEO exhibits potent antiradical activity (IC50 = 148.33 ± 2.48 μg/mL) and significant antioxidant capacity (TAC = 171.56 ± 2.34 μg AA/mg of EO). It demonstrates notable antibacterial activity against four strains (Staphylococcus aureus, Micrococcus luteus, Escherichia coli, and Pseudomonas aeruginosa) with inhibition zones ranging from 18.70 ± 0.30 mm to 29.20 ± 0.30 mm, along with relatively low MIC and MBC values. LPEO displays significant antifungal activity against four strains (Candida glabrata, Rhodotorula glutinis, Aspergillus niger, and Penicillium digitatum) with a fungicidal effect at 1 mg/mL, surpassing the positive control (cycloheximide), and MIC and MFC values indicating a fungicidal effect. It exhibits substantial inhibition of xanthine oxidase enzyme (IC50 = 26.48 ± 0.90 μg/mL), comparable to allopurinol, and marked inhibitory effects on α-amylase (IC50 = 31.56 ± 0.46 μg/mL) and α-glucosidase (IC50 = 58.47 ± 2.35 μg/mL) enzymes.The enzyme tyrosinase is inhibited by LPEO (IC50 = 29.11 ± 0.08 mg/mL). LPEO displays moderate cytotoxic activity against breast, liver, and colon cancer cells, with low toxicity towards normal cells (PBMC). LPEO exhibits greater selectivity than cisplatin for breast (MCF-7) and colon (HCT-15) cancer cells but lower selectivity for liver (HepG2) and metastatic breast (MDA-MB-468) cancer cells. These findings suggest the potential of LPEO as an antioxidant, antimicrobial, anti-gout, antidiabetic, and anticancer agent.